HELEN KELLER’S STRUGGLE IN THE STORY OF MAY LIFE - Ardhinie, Eka; Hartati, Sri (Universitas Gunadarma, 2012)
One of the literary works is novel. In the novel we can find many kinds of character.This research aims to find out the characteristics of Helen Keller by usingpsychological approach and to describe the factors influence Helen Keller tostruggle in obtaining the equal confession as usual human. This research usedqualitative method in analyzing the data. The data is taken from Helen Keller’sNovel “The Story of My Life” and in the form of quotation from novel that relatedto Helen Keller’s characters. The result of this research are the characteristics ofHelen Keller in term of angry, naughty, curiosity, struggle, eager, clever, dilligent,care, confident, brave, independent. There are also some factors that influence thecharacteristics of Helen Keller, such as: Influence from family, teacher and famouspeople.